SCIENTIFIC APPROACHES TO UNDERSTANDING THE MODEL, TYPE AND FORM OF THE CRIMINAL PROCESS - Пєсцов, Руслан; Дубчак, Леся; Гавронська, Тетяна; Горінов, Павло; Деркачова, Наталія (SWorldJournal, 2024)
The article examines the historical forms of the criminal process in the context of international scientific directions. The dependence of the form of the process on the state ( level of individual freedom), political regime, the level of legal culture i